Modeling, Simulation, and Performance Analysis of Decoy State Enabled Quantum Key Distribution Systems - Mailloux, Logan; Grimaila, Michael; Hodson, Douglas; Engle, Ryan; McLaughlin, Colin; Baumgartner, Gerald (Applied sciences, 2017)
Quantum Key Distribution (QKD) systems exploit the laws of quantum mechanics to generate secure keying material for cryptographic purposes. To date, several commercially viable decoy state enabled QKD systems have been successfully demonstrated and show promise for high-security applications such as banking, government, and military environments. In this work, a detailed performance analysis of decoy state enabled QKD systems is conducted through model and simulation of several common decoy state configurations. The results of this study uniquely demonstrate that the decoy state protocol can ensure Photon Number Splitting (PNS) attacks are detected with high confidence, while maximizing the system’s quantum throughput at no additional cost. Additionally, implementation security guidance is provided for QKD system developers and users.